Transborylation-Enabled Boron Catalysis - Bage, Andrew D.; Nicholson, Kieran; Hunt, Thomas A.; Langer, Thomas; Thomas, Stephen P. (Synthesis, 2022)
This review highlights transborylation (controlled boron-boron exchange) and its applications as a turnover strategy in boron-catalysed methodologies. Catalytic applications of B–C, B–O, B–N, B–F, B–S, and B–Se transborylations are discussed in the context of transborylation-enabled catalysis, across a wide range of organic transformations including hydroboration, C–C bond formation, C–H borylation, chemoselective reduction, and asymmetric reduction.1 Introduction2 B–C Transborylation3 B–O Transborylation4 B–N Transborylation5 B–F Transborylation6 B–S Transborylation7 Conclusion
Keywords: transborylation; boron; main group; catalysis; metathesis